Efeito da simpatectomia química sobre as vértebras de ratas osteopênicas induzidas pela ovariectomia - Wang, Charles Chenwei (Universidade Federal de São Carlos, 2005)
Osteoporosis is a pathology that afflicts mainly postmenopausal women, consequently this disorder generates severe social and economic consequences. This disease is characterized by low bone mass (osteopenia) and bone tissue microarchitectural deterioration, which leads to enhanced bone fragility, thus resulting in fracture risk increase. As an experimental mode of bone loss in post-menopausal women the ovariectomized rat has been used. The periosteum is innervated by sympathetic nervous system (SNS) whose neurotransmitters regulate direct and indirectly the bone metabolism. In this study, we evaluated the possible influence of SNS on physical, biometric, biomechanical and biochemical parameters of the 5th lumbar vertebrae of ovariectomized (ovx) rats. Therefore, 4-month-old female rats were randomized in 5 groups: Basal (sacrificed at the beginning of the experimental), Intact (treated with 0,9% saline, sc), Control (ovx rats treated with 0,9% saline, sc), GUA 30 (ovx rats treated with 37 mg of guanetidine /kg, sc, for 30 days) and GUA 8 (ovx rats treated with 40 mg of guanetidine /kg, sc, for 8 weeks). The animals were sacrificed at the end of 8 weeks, except for the Basal group. The 5th lumbar vertebra was removed and defleshed and physical, miometric, biomechanical and chemical properties were analyzed. The denervation was confirmed by palpebral ptose and diarrhea observed in all treated animals. The Control group showed lower mineral and bone densities than the Intact group with consequent lower biomechanical parameter, indicating that castration was effective to induce osteopenia. The sympathetic denervation partially inhibited the osteopenia as shown by the higher values of mineral and bone densities when compared with the Control group. But, these better physical parameters did not induced better bone quality as shown by biomechanics.
Keywords: Medicina experimental - rata; Osso; Ovariectomia; Osteoporose; Sistema nervoso autônomo; CIENCIAS BIOLOGICAS::FISIOLOGIA